Identification of orthotropic plastic material parameters for deep-drawing steel using DIC and FEMU - Schmaltz, Stefan; Willner, Kai (COMPLAS XI Proceeding (CD), 2011)
In this paper the deep-drawing sheet steel DC04, representative for sheet-bulk metal forming processes, is characterized through uni- and biaxial tensile and compression tests. The orthotropic plastic material parameters for the Hill 1948 yield surface are identified in two different ways. The first one utilizes uniaxial tensile experiments with specimen in three angles to the rolling direction of the sheet (0, 45 and 90 degree) and the plastic material parameters are calculated through the Lankford coefficients. Second a Finite Element Model Updating (FEMU) procedure is introduced. By taking the measured full-field displacement data and the forces of the biaxial tensile experiments better fitting parameters are identified at reasonable experimental costs.
UnivIS-Import:2015-04-16:Pub.2011.tech.FT.FT-TM.identi
Keywords: Computational Plasticity; FEMU; Parameter Identification; Sheet steel